Conventional methods of piston surface treatment for IC engines - Sanja Trgovčević; Karlo Raić (Zaštita Materijala)
This paper provides an overview of conventional methods of piston surface treatment for IC engines. One of the most stressed parts of IC engine is the cylinder assembly, i.e., the piston as a component of this assembly. In its operation, the piston is exposed to the impact of aggressive gaseous and liquid environment, elevated temperatures, thermal shocks and mechanical loads. The analysis of these methods has shown that the surface coatings that are created on certain surfaces on the piston substantially increase the tribological performance and extend the lifetime of the piston.